LINGVOPOETIC NATURE OF PHRASEOLOGIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the given paper phraseologisms which are appeared in Erkin A’zam works was analyzed and their lingvopoetic investigations were showed with certain examples.